Electrospun polymer nanofibers - Arinstein, Arkadii (Pan Stanford Publishing, 2018)
Annotation Discussing the electrospinning process, the book covers in great depth the current research interest in nanoscience and nanotechnology, especially electrospinning of polymer nanofibers. The main distinction of the proposed book from others devoted to the electrospinning process is in the consideration of the problem in question from the physical point of view. Focusing on physical aspects, the book contains physical basics regarding the unique features of electrospun polymer nanofibers and the electrospinning resulting in fabrication of these nanofibers.
Keywords: Nanofibers.; Electrospinning.; Nanostructured materials.; elektronické knihy; electronic books